Does initial postgraduate career intention and social demographics predict perceived career behaviour? A national cross-sectional survey of UK postgraduate doctors - Jennifer Cleland; Kim Walker; Peter Johnston; Gillian Marion Scanlan; Suzanne Anderson Stirling (BMJ Open)
Objective Studies indicate that initial career intentions and personal characteristics (eg, gender) can influence medical career decision-making. However, little is known about how personal characteristics and intention interact with career decision-making. To address this gap, we examined the link between career intention at the start of the 2-year UK Foundation Programme (FP) and career intentions on its completion.Methods Data came from the 2017 UK National Career Destination Survey, a cross-sectional study completed by all second year foundation doctors. We included respondents’ demographics (gender, graduate status on entry to medical school, career intention on starting the FP) and career intention as an outcome measure (eg, specialty (residency) training (UK), NHS non-training posts/further study, career break, working abroad). Multinomial regression was used to assess the independent relationship between background characteristics and career intention.Results There were 6890 participants and 5570 usable responses. 55.9% of respondents were female and 43.1% were male, 77.1% were non-graduates and 22.9% were graduate entrants to medical school. Approximately two-thirds (62.3%, n=2170) of doctors who had an original intention to pursue specialty training after F2, still intended to do so on completion. Most of those who stated at the start of F2 that they did not want to pursue specialty indicated at the end of F2 they would be undertaking other employment opportunities outwith formal training. However, 37.7% of respondents who originally intended to pursue specialty training on FP completion did something different. Graduate entrants to medicine were more likely to immediately progress into specialty training compared with their peers who did medicine as a primary first degree.Conclusion Original intention is a strong predictor of career intentions at the end of the FP. However, a considerable proportion of doctors changed their mind during the FP. Further research is needed to understand this behaviour.